Factors influencing undergraduate academic performance of Universiti Teknologi MARA (UiTM) Kelantan Branch / Mariam Setapa … [et al.] - Setapa, Mariam; Rahman, Khairunnisa; Kamarul Zaman, Liziana; Wan Mustapha, Wan Asma Hanim; Mohamad, Siti Sarah; Ab Rahman, Siti Maziah (2021)
Academic performance is a vital issue that entails the same attention from groups despite the differentiation in political interest and intention. In light of this issue, this research is undertaken to discover the performance of diploma students in the Faculty of Business and Management, Universiti Teknologi MARA Kelantan Branch (UiTMCK), Malaysia. Furthermore, this study determines the relationship between factors and academic performance in UiTMCK. By using simple random sampling, the data were collected from 100 students from Diploma of Business Studies through a questionnaire survey. The data were analyzed using SmartPLS 3.2.1 software. The analysis showed that only group discussion, self-motivation and family influence had a strong direct relationship with academic performance while the rest of the variables did not have a significant relationship with academic performance. The implication from this study would be of benefit for future researcher who are interested in examining other indicators of measuring students’ performance such as communication, problem-solving and teamwork skills.